1994
DOI: 10.3354/dao020077
|View full text |Cite
|
Sign up to set email alerts
|

Perkinsus marinus (Apicomplexa) as a potential source of oyster Crassostrea virginica mortality in coastal lagoons of Tabasco, Mexico

Abstract: NOTEPerkinsus marinus (Apicomplexa) as a potential source of oyster Crassostrea virginica mortality in coastal lagoons of Tabasco, Mexico Eugene M. Burreson', Raul Sima ~l v a r e z~, Victor Vidal ~a r t i n e z~, Leopoldina Aguirre ace do^

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 3 publications
1
30
0
1
Order By: Relevance
“…Even though previous studies reported P. marinus from the Mexican coast, little research has been done over a long-term period in this tropical area. When the parasite was discovered by Burreson et al (1994) in Tabasco, few samples were assayed (mainly gapers), and despite the high prevalence (60 to 100%), the infection intensity was light to moderate except in one location in Machona Lagoon. Because water samples and/ or hemolymph were not collected, it is difficult to draw a definite conclusion about different environmental or physiological conditions with respect to Terminos Lagoon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though previous studies reported P. marinus from the Mexican coast, little research has been done over a long-term period in this tropical area. When the parasite was discovered by Burreson et al (1994) in Tabasco, few samples were assayed (mainly gapers), and despite the high prevalence (60 to 100%), the infection intensity was light to moderate except in one location in Machona Lagoon. Because water samples and/ or hemolymph were not collected, it is difficult to draw a definite conclusion about different environmental or physiological conditions with respect to Terminos Lagoon.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical areas, the behavior of P. marinus has not been widely documented. In Mexico, the first report of P. marinus was by Burreson et al (1994) in Tabasco after a mortality event suspected to have been caused by pollutants from an oil refinery close to CarmenPajonal-Machona and Mecoacan Lagoons. These authors demonstrated the existence of P. marinus in the 3 lagoons with 90 to 100% prevalence at high salinity sites (30 psu) and 50% at low salinity sites (15 psu).…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first described, Perkins~is n~arinus has been associated with oyster Crassostrea virginica mortalities (Burreson et al 1994, Andrews 1996. It was believed to be a fungus and was given the name Der~nocystidium marinum (Mackin et al 1950).…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration among the three researchers resulted in description of this unknown agent as Dermocystidium marinum (Dermo), which is now called Perkinsus marinus. To date, this pathogen has been identified in native oysters, Crassostrea virginica, along the Atlantic coast of the United States and Mexico, from Maine a Corresponding author: villalba@cimacoron.org (Ford 1996) to Tabasco, in the Gulf of Mexico (Burreson et al 1994a;Andrews 1988;Soniat 1996).…”
Section: Historical Perspectivementioning
confidence: 99%